The health situation of adolescents: a literature review - Ali, Ahmed; Mahmud, Shah Noor (BRAC Research and Evaluation Division (RED), 2019)
This review paper addresses the health situation of the adolescents. Most of the studies we found were conducted in countries other than Bangladesh. The medical care of the adolescent has always been neglected in the developing world until recently. While their medical needs are now being considered with an increased emphasis, their phychosocial needs, which are so important have not been adequately addressed. A few studies have been conducted in Bangladesh on issues of reproductive health. These studies suggests that early marriage is a serious problem for adolescent girls resulting in early pregnancy and thus enhances other reproductive health problems.